Managing Resource Capacity Using Hybrid Simulation - Norazura, Ahmad; Noraida, Abdul Ghani; Anton Abdulbasah, Kamil; Razman, Mat Tahar (2014)
Due to the diversity of patient flows and interdependency of the emergency department (ED) with other units in hospital, the use of analytical models seems not practical for ED modeling. One effective approach to study the dynamic complexity of ED problems is by developing a computer simulation model that could be used to understand the structure and behavior of the system. Attempts to build a holistic model using DES only will be too complex while if only using SD will lack the detailed characteristics of the system. This paper discusses the combination of DES and SD in order to get a better representation of the actual system than using either modeling paradigm solely. The model is developed using AnyLogic software that will enable us to study patient flows and the complex interactions among hospital resources for ED operations. Results from the model show that patients’ length of stay is influenced by laboratories turnaround time, bed occupancy rate and ward admission rate.